Periarticular Steroid Injection in Sacroiliac Joint Pain Patients with Ultrasound Guidance: A Case Report - Muhammad Nala; Alamsyah Ambo Ala Husain (Journal of Anesthesiology and Clinical Research, 2023)
Introduction: Pain in the sacroiliac joint area is pain below the level of the sacroiliac joint. L5 without symptoms of numbness or paresthesias and lower back pain that is aggravated after prolonged sitting, bending forward, and transitioning from sitting to standing. This study aims to describe cases of sacroiliac joint pain treated with periarticular steroid injection. Case presentation: A man, 47 years old, came with a complaint of pain in the right buttock area. The pain has been felt since 1 month ago. The pain is felt continuously and gets worse when standing for a long time while working. The pain radiates to the right thigh and calf. The patient was diagnosed with sacroiliac joint pain. The patient is then prepared for an ultrasound-guided steroid injection. The drugs injected were triamcinolone 40 mg 1 mL and Bupivacaine 0.5% 3 mL with the help of a linear ultrasound probe Conclusion: The procedure of sacroiliac joint injection provides a significant pain reduction response in sacroiliac joint pain.